Implementation of the Problem Based Learning (PBL) Model in Islamic Religious Education Learning and Its Implications for the Critical Thinking Ability of Students of SMAN 1 Rejang Lebong - Pransiska, Selvi; Sari, Dewi Purnama; Nasution, Aida Rahmi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Education plays an important role in human life, so improving in all aspects is needed, both in terms of teachers as educators and students. Education, which as an effort to humanize humans, must be able to help humans develop their potential. This study aims to find out implementation of the problem based learning (PBL) model in islamic religious education learning and its implications for the critical thinking ability of students of sman 1 rejang lebong. This research uses a descriptive method of Analysis with a type of qualitative research, which is a type of research that describes phenomena or facts on the object under study to take the essence of each phenomenon. Problem Based Learning implementation model which includes planning, implementation and evaluation. The study of Religious Education at SMAN 1 Rejang Lebong is to prepare the appointment of annual learning programs, semester programs, syllabus, lesson plans, and selection of teaching materials. The implementation of the Problem Based Learning Model in teaching Islamic Religious Education is to convey basic competencies and teaching objectives. Keidua, divide students into groups. Third, show students to discuss the problem presented. Fourth, convey the results of the discussion to the front of the class and to other listening groups, while the other group is given the opportunity to speak, imitate suggestions, criticisms, and input. After the presentation is over. Fifth, the teacher evaluates the results of the discussion.